ANALISIS KESIAPAN SEKOLAH DALAM MENERAPKAN MODEL PEMBELAJARAN BLENDED LEARNING PADA PEMBELAJARAN MATEMATIKA - Ni Made Rai Dwi Lestari; I Made Wena; I Gusti Ayu Putu Arya Wulandari (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan Unmas Denpasar, 2022)
ABSTRACT The purpose of this research is to find out how the readiness of Saraswati 1 Denpasar High School (SLUA) in the application of blended learning models in mathematics learning, to find out the supporting factors in the readiness of the blended learning application in mathematical learning, and to know the supporting factors in the readiness of the application of blended learning models in mathematical learning. This research is descriptive qualitative research with a research sample consisting of the headmaster, math teacher, and science students. These research instruments use questionnaires and interview sheets. The results showed that Saraswati 1 Denpasar High School (SLUA) is classified as a ready school in applying the blended learning model to mathematical learning, but the school needs more improvement in each readiness factor developed by Aydin & Tasci. There are some supporting factors in applying the blended learning model in mathematical learning, namely human factors in the experience criteria to implement blended learning; technological factors on the attitude criteria in using technology for blended learning; and innovation factors on the criteria for adjustment of the teacher's ability to plan the blended learning as well as the ability of students to follow the blended learning model. There are factors that inhibit the development of blended learning models in mathematical learning, namely technological factors on the criteria of the availability of facilities and infrastructure for the blended learning. Keywords: Readiness Analysis; Blended Learning; Mathematical Learning ABSTRAK Tujuan penelitian ini adalah untuk mengetahui bagaimana kesiapan SMA (SLUA) Saraswati 1 Denpasar dalam penerapan model pembelajaran blended learning pada pembelajaran matematika, untuk mengetahui faktor-faktor pendukung dalam kesiapan penerapan model pembelajaran blended learning pada pembelajaran matematika, dan untuk mengetahui faktor-faktor penghambat dalam kesiapan penerapan model pembelajaran blended learning pada pembelajaran matematika. Penelitian ini merupakan penelitian kualitatif deskriptif dengan sampel penelitian terdiri dari kepala sekolah, guru matematika, dan siswa jurusan IPA. Instrumen penelitian ini menggunakan kuesioner dan lembar wawancara. Hasil penelitian menunjukkan bahwa kesiapan SMA (SLUA) Saraswati 1 Denpasar dalam menerapkan model pembelajaran blended learning pada pembelajaran matematika tergolong siap namun perlu sedikit peningkatan pada setiap faktor kesiapan yang dikembangkan oleh Aydin & Tasci. Terdapat faktor-faktor pendukung penerapkan model pembelajaran blended learning pada pembelajaran matematika yakni faktor manusia pada kriteria pengalaman untuk melaksanakan blended learning; faktor teknologi pada kriteria sikap dalam menggunakan teknologi untuk pembelajaran blended learning; dan faktor inovasi pada kriteria penyesuaian kemampuan guru dalam merencanakan pembelajaran blended learning serta kemampuan siswa dalam mengikuti pembelajaran blended learning. Terdapat faktor penghambat penerapkan model pembelajaran blended learning pada pembelajaran matematika yakni faktor tenologi pada kriteria ketersediaan sarana dan prasarana untuk blended learning. Kata Kunci: Analisis Kesiapan; Blended Learning; Pembelajaran Matematika